2019
DOI: 10.37358/rc.19.1.6876
|View full text |Cite
|
Sign up to set email alerts
|

Contributions on the Sensorial, Physico-chemical and Nutritional Characterization of Hare Meat (Lepus europaeus pallas)

Abstract: The growing demand for food worldwide, along with the increasing need for animal protein, lead to the identification of other sources of highest quality meat, then the conventional ones, such as it is the hare meat. The aim of this study was to characterize the sensorial, physico-chemical and nutritional traits of hare meat (Lepus europaeus Pallas) issued from hunting funds in North-East of Romania. The biological material consisted of 79 hares (34 males and 45 females), slaughtered by shooting at the age of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…The extraction of lipids from meat samples was performed with a mixture of chloroform and methanol (2:1 v/v), as described by Folch [24]. Next, lipid extracts were converted to fatty acid methyl esters (FAME) through a consecutive trans-esterification with methylene chloride [25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…The extraction of lipids from meat samples was performed with a mixture of chloroform and methanol (2:1 v/v), as described by Folch [24]. Next, lipid extracts were converted to fatty acid methyl esters (FAME) through a consecutive trans-esterification with methylene chloride [25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…So, an optimal FA profile has been shown particularly during early spring, when fresh spontaneous vegetation is available, which increases the amount of PUFA, particularly n-3, and lower SFA and MUFA concentration, as demonstrated in wild rabbits hunted in Greece [36]. Additionally, there are differences on some FA depending on sex [46].…”
Section: Small Gamementioning
confidence: 96%
“…Considering the variability for each of the parameters mentioned above, it is clear that the available food where animals are harvested has a significant influence on meat composition. On the other hand, some studies have found that several factors influence protein and fat content, and consequently energetic value, the most important being: (i) sex, as meat from females has a higher fat content and lower protein content [45,46]; (ii) the hunting period, with higher fat and protein content in winter compared to spring [47]; (iii) muscle type, with a higher fat content in the legs compared to the loin [37,46].…”
Section: Small Gamementioning
confidence: 99%
See 1 more Smart Citation
“…The working methods used were mainly the specific ones used to determine the nutritional value of the worm leaf and they were based on the chemical composition (the proximate analysis scheme), the digestibility of its components (the in vivo method -simple digestibility, with a single control period) and crude energy (use of specific computation equations and regression coefficients recommended by the OKIT system), digestible (calculation equation recommended for monogastric species) and metabolizable (equations recommended for monogastric animals and birds) contained [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Experimental Partmentioning
confidence: 99%